Infecção por Cryptosporidium em aves - Uma revisão - Nakamura, Alex Akira [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (FapUNIFESP (SciELO), 2015)
Cryptosporidiosis is one of the main protozoan infections in birds. It manifests as either a respiratory or a digestive illness, and it affects a very large number of avian species across several continents. The aim of this review is to report on the main results of studies on cryptosporidiosis among birds and the importance of these results to veterinary medicine and public health.
Cryptosporidium infections in birds - A review
Keywords: Cryptosporidium spp; Poultry; Wild birds